Appraising praise: experimental evidence on positive framing and demand for health services. Issue 7 (16th April 2021) - Anteneh, Aderaw; Bidwell, Kelly; Girma, Woldemariam; Little, Kristen; Wilson, Nicholas; Workalemahu, Endale
ABSTRACT: Standard economic models of human behaviour take the view that non-informative elements of communication (e.g. tone) do not affect behaviour. Casual observation of consumer and producer behaviour, as well as descriptive evidence, suggests this may be an overly strong assumption in many contexts, including healthcare. For example, 59% of female respondents in the 2011 Ethiopia Demographic and Health Survey reported that 'rude attitude of health provider' was a major problem that prevented them from seeking medical advice and treatment. Yet there is only a small body of evidence on the causal effects of non-informative elements of communication from real-world settings. We conducted a field experiment with over 800 HIV+ female sex workers (FSWs) in Ethiopia testing the effects of providing of Praise Message phone calls on retention in antiretroviral (ART) care and adherence to ART medication. We find mixed evidence on the effects of Praise Messages, suggesting further investigation into the effects of praise or other non-informative communication on health behaviour.